Pemanfaatan Google Custom Search Untuk Pencarian Satu Pintu Koleksi Perpustakaan BPPT - Putri Ayu Pramesti (Pustakaloka, 2019)
The Library of Technology Assessment and Application has several collection repositories that are stored on different applications and servers. In searching for collections that are needed, users must search for in each application. There is not yet a single way to search all of this content at once, therefore required a single way searching through all repositories so that users can easily find the information needed. In this study, the Google Custom Search   plugin was used to build a one-door search portal, so users can search collections in multiple repositories through single way. The results showed that this plugin can be used to build a one-door search portal. The use of the Google Custom Search   plugin is easy and simple. The results of the search showed collections from each repository according to the keywords entered.